Baptists and the Holy Spirit : The Contested History with Holiness-Pentecostal-Charismatic Movements - Weaver, C. Douglas (Book collections on Project MUSE., 2019)
"Connects American Baptists with the charismatic movement and charts Baptist perspectives on the Holy Spirit"--